The Urgency of Agency Theory in Minimizing Financial Fraud: A Case Study in the Construction Industry - Yudha Pramana; Anis Wahyu Hermawan (The Scientia Journal of Economics Issues, 2022)
Fraud that still occurs in certain corporations, including in specific construction industries, is a problem that must be addressed in the current era of good corporate governance (GCG). Based on secondary data and with a qualitative approach, it is concluded that the weakness of corporations in applying agency theory has led to fraud in the form of motives, incentives, opportunities, and rationalizations carried out by agents. In comparison, one of the implementations of agency theory in tackling fraud in financial statements is to apply accountability through contractual relationships that are strictly binding on agents and principals.